Clot perviousness is associated with first pass success of aspiration thrombectomy in the COMPASS trial. (17th July 2020) - Mokin, Maxim; Waqas, Muhammad; Fifi, Johanna; De Leacy, Reade; Fiorella, David; Levy, Elad I; Snyder, Kenneth; Hanel, Ricardo; Woodward, Keith; Chaudry, Imran; Rai, Ansaar T; Frei, Donald; et al.
Abstract : Background: Clot density (Hounsfield units, HU) and perviousness (post-contrast increase in the HU of clot) are thought to be associated with clot composition. We evaluate whether these imaging characteristics were associated with angiographic outcomes of aspiration and stent retriever thrombectomy in COMPASS: a trial of aspiration thrombectomy versus stent retriever thrombectomy as first-line approach for large vessel occlusion. Methods: Clot density and perviousness were measured by two independent operators who were blind to all the final angiographic and clinical outcomes. The association of clot density and perviousness with the Thrombolysis In Cerebral Infarction (TICI) scale after first pass was assessed using univariate and multivariate analysis. Results: Among all patients enrolled in COMPASS, 165 were eligible for the post-hoc analysis (81 patients in the aspiration first and 84 in the stent retriever first groups). Overall mean perviousness of clot was significantly higher in patient with mTICI 2b-3 after first pass (28.6±22.9 vs 20.3±19.2, p=0.017). Mean perviousness among patients who achieved TICI 2c/3 versus TICI 2b versus TICI 0-2a in the aspiration first group varied significantly (32.6±26.1, 35.3±24.4, and 17.7±13.1, p=0.013). The association of perviousness with first pass success was not significant in the stent retriever group. Using multivariate analysis, high perviousness (defined as cut-off >27.6) was an independent predictor of TICI 2b-3 (OR 3.82, 95% CI 1.10 to 13.19; p=0.034). Conclusions: Clot perviousness is associated with first pass angiographic success in patients treated with the aspiration first approach for thrombectomy.